HUBUNGAN POWER OTOT LENGAN DAN BAHU DENGAN HASIL TOLAK PELURU PADA SISWA PUTRA KELAS XI IPS SMA PEMBANGUNAN KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR - Arifuddin Arifuddin; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on observations on male students of class XI IPS of SMA Development in Bagan Sinembah Subdistrict, Rokan Hilir Regency, problems often arise in the observations that the author made when conducting a shot putter test is the maximum in repulsion, this is caused by the non-maximum power of the arm muscles and shoulder. The purpose of this study was to determine whether there is a Relationship between Arm and Shoulder Muscle Power with Bullet Resistant Results in Male Students Class XI IPS SMA Pembangunan Bagan Sinembah District, Rokan Hilir Regency. The population in this study were male students aged 15-17 years old class XI IPS SMA Pembangunan Kecamatan Bagan Sinembah, Rokan Hilir Regency, totaling 32 people. The sampling technique uses total sampling technique. The instruments in this study were two hand medicine ball put and shot put. The results obtained were analyzed using produck moment correlation. Based on the results of research conducted and have gone through a statistical data processing process, it can be concluded that there is a relationship between arm and shoulder muscle power with the result of shot putting in male students of class XI IPS in SMA Development, Bagan Sinembah Subdistrict, Rokan Hilir District with Nilair xy = 0.233. There is a relationship between variable X with variable Y with a low category in the range 0.20 to 0.399 seen from the interpretation table.Key Words: Arm and Shoulder Muscle Power, Bullet Resist Results